Aerial photogrammetry and tag-derived tissue density reveal patterns of lipid-store body condition of humpback whales on their feeding grounds. Issue 1943 (27th January 2021) - Aoki, Kagari; Isojunno, Saana; Bellot, Charlotte; Iwata, Takashi; Kershaw, Joanna; Akiyama, Yu; Martín López, Lucía M.; Ramp, Christian; Biuw, Martin; Swift, René; Wensveen, Paul J.; Pomeroy, Patrick; et al.
Abstract : Monitoring the body condition of free-ranging marine mammals at different life-history stages is essential to understand their ecology as they must accumulate sufficient energy reserves for survival and reproduction. However, assessing body condition in free-ranging marine mammals is challenging. We cross-validated two independent approaches to estimate the body condition of humpback whales ( Megaptera novaeangliae ) at two feeding grounds in Canada and Norway: animal-borne tags ( n = 59) and aerial photogrammetry ( n = 55). Whales that had a large length-standardized projected area in overhead images (i.e. whales looked fatter) had lower estimated tissue body density (TBD) (greater lipid stores) from tag data. Linking both measurements in a Bayesian hierarchical model to estimate the true underlying (hidden) tissue body density (uTBD), we found uTBD was lower (−3.5 kg m −3 ) in pregnant females compared to adult males and resting females, while in lactating females it was higher (+6.0 kg m −3 ). Whales were more negatively buoyant (+5.0 kg m −3 ) in Norway than Canada during the early feeding season, possibly owing to a longer migration from breeding areas. While uTBD decreased over the feeding season across life-history traits, whale tissues remained negatively buoyant (1035.3 ± 3.8 kg m −3 ) in the late feeding season. This study adds confidence to the effectiveness of these independent methods to estimate the body condition of free-ranging whales.